Social Entrepreneurship with Digital Literacy in The Digital Era 4.0 (Systematic Literature Review) - Choirunnisa, Salsabila Safitri; Fransisca Ucik Pudjiastuti; Andy Prasetyowati; Ludi Wishnu Wardana; F Danardana Murwani (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This research aims to explore the relationship between social entrepreneurship and digital literacy in the digital 4.0 era, focusing on understanding the importance of digital literacy integration in accelerating innovation and creating greater social impact as well as raising public awareness of the importance of digital literacy and the creation of social entrepreneurship. Design/methodology/approach: The research method used is a systematic literature review to analyze the relationship. Research Findings: The results show that digital literacy plays a key role in developing social entrepreneurship, enabling access to digital business opportunities, improving operational efficiency, and expanding market reach globally. Theoretical Contribution/Originality: In conclusion, the integration of digital literacy in social entrepreneurship is an important strategy to create social value and raise public awareness of social and environmental issues in the current digital era.